The role of Foxp3 and Tbet co-expressing Treg cells in lung carcinoma - Kachler, Katerina; Holzinger, Corinna; Trufa, Denis; Sirbu, Horia; Finotto, Susetta (OncoImmunology, 2018)
Despite the opposite roles of Tbet and Foxp3 in the immune system as well as in tumour biology, recent studies have demonstrated the presence of of CD4+ T cells, expressing both, Tbet and Foxp3. Although Tbet+Foxp3+ T cells are currently a subject of intense research, less is known about their biological function especially in cancer. Here we found a considerable accumulation of Tbet+Foxp3+CD4+ T cells, mediated by the immunosuppressive cytokine TGFβ in the lungs of tumour bearing mice. This is in line with previous studies, demonstrating the important role of TGFβ for the immunopathogenesis of cancer. By gathering results both in murine model and in human disease, we demonstrate that, the conversion of IFNγ producing anti-tumoral T-bet+Th1 CD4+ T cells into immunosuppressive Tbet and Foxp3-PD1 co-expressing regulatory cells could represent an additional important mechanism of TGFβ-mediated blockade of anti-tumour immunity.
EVALuna2:35735